Design And Development Of Basic Learning Modules For Open-Source Jaamsim Discrete Event Simulation Software - Angles, Liew Xin Juan (Universiti Sains Malaysia, 2017)
This project is about designing and developing a basic learning module of open-source JaamSim (“Java Animation Modelling and Simulation”) discrete event simulation software. One of the difficulties faced by the users when using simulation softwares is the accessibility of the software, especially for the students who were always struggling in obtaining the license of the softwares. Besides, for the users who wanted to learn new simulation softwares, the learning resources available are limited. In this project, JaamSim simulation software was being chosen as it is an open-source software which is free. Its features can be comparable with other commercial discrete event simulation softwares such as WITNESS. Generally, this project was conducted based on the “ADD” (Assessment-Design-Development) concept. First of all, the learning needs of the software users were being determined through online survey. The target of the survey respondents in this project were students from Universiti Sains Malaysia (USM) who are studying the course of Manufacturing Engineering with Management. The project was then followed by the analysis of learning needs of users. Next, the JaamSim software was being studied, and five simulation models were built based on the manufacturing examples. The basic learning modules were then being designed and developed based on the learning needs of users. Videos are also being made for the learning modules using “Powtoon” software. In the end of this project, the basic learning modules should reach the learning needs of the users when using JaamSim discrete event simulation software.